E-028 The impact of time delays on endovascular reperfusion success in late window stroke patients. (23rd July 2022) - Alhabli, I; Benali, F; Murphy, S; Toni, D; Michel, P; Hill, M; Herlihy, D; Casetta, I; Power, S; Saia, V; Hegarty, A; Pracucci, G; et al.
Abstract : Introduction: Delays have a negative impact on successful reperfusion with endovascular thrombectomy (EVT) in early-window strokes. Late window patients may be further disadvantaged due to their late presentation. We assessed the impact of delays on reperfusion success in late window stroke patients. Materials and Methods: We pooled data from seven trials and registries in North America, Europe, and Korea, for anterior circulation stroke patients treated with EVT between 6 and 24 hours from onset. We explored the impact of delays across multiple time metrics, including onset (or last known well) to hospital arrival; hospital arrival to arterial puncture; and CT to arterial puncture. Our primary outcome was successful reperfusion, defined as a final thrombolysis in cerebral infarction (TICI) score of 2b-3. Univariable and multivariable logistic regression analyses were performed to assess the association between each of the time metrics and successful reperfusion; adjusting for age, sex, occlusion site, NIHSS score, and wake-up stroke status. Results: We included 608 patients. The median age was 70 years (IQR: 21), 307 [50.2%] were females, and 311 (53.2%) had wake-up strokes. All patients had CT and CT angiography imaging, and 379 patients (62.3%) also underwent perfusion imaging. Successful reperfusion was achieved in 494 (81.2%) patients. Patients with successful reperfusion were more likely to have had wake-up strokes (55.7% versus 42.7%, p=0.02) and lower NIHSS scores (median 15 [IQR 8] versus 17 [10], p=0.02) compared to unsuccessful reperfusion patients. Successfully reperfused patients had a significantly shorter hospital arrival to arterial puncture time (90 minutes [60–150] versus 110 minutes [84.5–150], p=0.01) compared to unsuccessfully reperfused patients. The odds of successful reperfusion decreased by 6% for every one-hour delay in arrival to puncture (adjusted OR 0.94, 95% CI 0.89–0.99). The CT to puncture time was not different between the successful versus unsuccessful reperfusion patients in univariable and multivariable analyses (65 minutes [39–111] versus 66 minutes [46–105], p=0.33). The onset (last known well) to hospital arrival was longer in the successful reperfusion patients (555 minutes [412–692] versus 436 minutes [362–639.5], p=0.01). This difference, however, did not persist in the multivariable analysis (adjusted OR 1.07 for every one-hour delay, 95% CI 0.93–1.23). Conclusion: Faster hospital arrival to arterial puncture time is associated with a higher rate of successful reperfusion in late window stroke patients. Pre-hospital delays were not associated with subsequent reperfusion. Disclosures: I. Alhabli: None. F. Benali: None. S. Murphy: None. D. Toni: None. P. Michel: None. M. Hill: None. D. Herlihy: None. I. Casetta: None. S. Power: None. V. Saia: None. A. Hegarty: None. G. Pracucci: None. A. Demchuk: None. S. Mangiafico: None. K. Boyle: None. M. Goyal: None. S. Nannoni: None. E. Fainardi: None. J. Thornton: None. B. Kim: None. B. Menon: None. M. Almekhlafi: None. F. Bala: None.